Alleviation by leucovorin of the dose-limiting toxicity of edatrexate: potential for improved therapeutic efficacy - Lee, J S; Murphy, W K; Shirinian, M H; Pang, A; Hong, W K (Cancer chemotherapy and pharmacology, 1991)
Edatrexate (10-ethyl-10-deaza-aminopterin; CGP 30 694) is a methotrexate (MTX) analogue that shows promise against non-small-cell lung cancer (NSCLC) and other tumors. Since edatrexate's mechanism of action is the same as that of MTX, we used leucovorin in an attempt to alleviate its dose-limiting toxicity, stomatitis. In four patients with NSCLC who had experienced significant stomatitis after treatment with edatrexate, cyclophosphamide, and cisplatin, we observed a remarkable reduction in stomatitis following the administration of low-dose leucovorin. On the basis of the results obtained in these individuals, we treated 15 additional patients with this three-drug regimen plus leucovorin rescue. These subjects could tolerate the treatment with lesser degrees of stomatitis and received higher edatrexate doses in subsequent courses as compared with the patients who previously received this regimen without leucovorin rescue. This approach is expected to improve the therapeutic indices of edatrexate and edatrexate-containing chemotherapy regimens by modifying the dose-limiting toxicity of this antineoplastic agent.